Applications of vibration-based energy harvesting (VEH) devices - Lee, O.B. (IGI Global, 2016)
This chapter reviews present usage of vibration-based energy harvesting (VEH) devices and applications. The evolution of energy resources and advance in electronic technologies has resulting the need of self-sustainable wireless/portable electronic devices in current modern society. Batteries are non-beneficial in the miniaturization process of electronic designing and alternative power supplies are desperately needed to fill in the falling behind technologies gap to drive the advance of the wireless/portable development further. VEH mechanism is suggested in this chapter as the solution for the bottleneck. Various consideration of creating an optimal vibration energy harvester are suggested through an analytical model of a mechanical transducer. Useful applications and usages of VEH are presented and some suggestion for improvement are also given. Lastly, the trend of energy harvesting is annotated and commented in-line with the demand of electronic sensors market. Â© 2017 by IGI Global. All rights reserved.